Discovery channel: raging planet : flood (Bethesda, MD : Discovery Communications, 1999)
This series will explore and illustrate the power and the beauty of our planet's natural hazards and dangers. It will travel to the ends of the Earth to record the best ever footage of floods, using new camera techniques and specialist equipment to go where no camera has gone before.